ADHD is awesome : a guide to (mostly) thriving with ADHD - Holderness, Penn; Holderness, Kim (Harper Horizon, 2024)
The must-have resource for anyone who lives with ADHD, either themselves or with an affected family member. Written to appeal to the ADHD brain, ADHD is Awesome is the engaging, uplifting antidote to traditional ADHD books (which, let's be honest if you have ADHD you'd never read anyway).